Media multitasking and cognitive control : assessing the feasibility of an intervention requiring the self-regulation of smartphone use - Parry, Douglas Anderson (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.